Do Municipal Facebook Performance and Citizen Satisfaction go Hand in Hand?. Issue 1 (2020) - Gellerstedt, Martin; Norström, Livia; Bernhard, Irene; Gråsjö, Urban; Snis, Ulrika Lundh
No abstract available